Endophytic mycobiota of genus Maxillaria Ruiz & Pav. (Orchidaceae) in two nature reserves of Quindío (Revista de Investigaciones Universidad del Quindío, 2016)
Previously orchids were considered generalists in their interactions  with  endophytes;  after the  breakthrough in the study of physiology it was assumed that there is some variation in their levels of specificity, even wi-   thin phylogenetically related species. In order to describe the endophytic mycobiota associated with the ge-    nus Maxillaria in two nature reserves in  Quindio.  Isolation  and taxonomic  characterization  of endophytes was carried out from 576 fragments of root tissue from orchids of the genus  Maxillaria. 268 inmates classi-  fied into 4 genres of endophytes were obtained; characterized macroscopically and microscopically; asylees genres most frequently were those relating to form  genus  Rhizoctonia, represented by  genus Ceratobasi-  dium and Tullasnela. Differences in the number of plant species colonized by sampling area and plants were observed. In conclusion, despite being a work based on morphotaxonomic characters, morphs of form genus Rhizoctonia are recorded in the study areas, in addition this work is the first Colombian contribution to sys- tematically documenting some aspects of the relationship fungus-orchid from Quindío and genus Maxillaria.
Keywords: Interaction; specificity; isolated; colonization; morphotaxonomic